Syntax und Semantik iin Erwerb zweitsprachlicher Fertigkeiten 37 Barbara SKOWRONEK, Zur Beschreibung der Fachsprachen für den gesteuerten Fremdsprachenunterricht - Figas, Janusz (Wydawcnictwo Naukowe UAM, 1986)
Action-oriented observation of the second language acquisition (L2-acquisi-tion) multiplies task setting in the organization of the L2-acquisition. A double problem has to be solved for three processes, namely Test I, Operation, and Test II (cf. TOTE-unit in Miller/Galanter/Pribram 1960) have to be normatively directed and also made functionally effective. Traditional division of syntax and semantics applied to the success and failure analysis does not seem to be sufficient. The verbal action in L2 should be considered in three aspects: normative regularity, functional reproductivity, and creativity.